Analisis Kualitas Kinerja Birokrasi SMA Negeri 1 Tarik Kecamatan Tarik Kabupaten Sidoarjo - PUTRI, SALSA BILAH (Magister Administrasi Publik FISIP Universitas Mulawarman, 2025)
Abstract: The study was intended to analyses the quality of performance of bureaucracy at state high school 1 attraction, Sidoarjo, Indonesia. The focus of this study is teacher performance in improving the quality of learning. This article emphasizes the importance of professional training and development for teachers to improve their performance. The concept of performance, both individual and organizational, and the importance of achieving goals are also discussed in this article. The research method used is a qualitative descriptive method. This article provides examples of the findings and conclusions related to teacher performance in improving the quality of learning at the state high school 1. Recommendations for further research and comprehensive reference lists are also presented. The study has significant implications in improving the quality of education at public high school 1 and may also be applicable in other schools. By understanding factors that affect teacher performance and identifying areas that need to be improved, schools can develop effective strategies to improve the quality of learning. Professional training and development for teachers also need attention so they can better teach and contribute to better results for students.Keywords: performance, organizational performance, teachers